Assessment of Some Heavy Metals and Pesticide Residues in Soil, Sediment, Clarias gariepinus and Oryza sativa Cultivated in Some Selected Agricultural Sites of Bauchi State, Nigeria - Mohammed, Umar Aminu; Kolo, Babagana; Shehu, Aishatu Aliyu; Hassan, Halima (CV. Literasi Indonesia, 2024)
Living organisms especially human beings get exposed to harmful substances such as heavy metals through the plants and animals we consume. Human sources of food like Oryza sativa and Clarias gariepinus get contaminated by the soil as a result of pesticides used by farmers. This study aimed to determine heavy metals levels and pesticide residue in soil, sediment, Oryza sativa, and Clarias gariepinus in three locations namely, Gadau, Jama’are, and Zabi (Giade LGA) in Bauchi State Nigeria. Samples of Soil, sediments, Oryza sativa, and Clarias gariepinus were collected at three different locations namely Gadau, Zabi, and Jamaare, to assess the level of some heavy metals and pesticide residues. The heavy metals present were detected in this order Zn>As>Pd>Cd>Cr>Ni in soil, sediment, Oryza sativa, and Clarias gariepinus respectively. The detected heavy metals were higher than the WHO/FAO recommended maximum tolerance values in three locations in this study. Among the active residues observed Abamectin and Dichlovos were more active compared to others with a 1- >5ppm range. The presence of these harmful substances in the environment is of serious concern to human health. This study recommends strict regulations on the use of pesticides for food crops and fish in the study area.